Cephalometrics of Pharyngeal Airway Space in Lebanese Adults. (4th January 2017) - Daraze, Antoine; Delatte, Myriam; Liistro, Giuseppe; Majzoub, Zeina
Abstract : Purpose . The upper airway space is significant in orthodontic diagnosis and treatment planning. The objectives of this study are to assess the dimensions of soft tissue elements of the upper pharyngeal space and evaluate potential correlations with modifying variables such as gender, skeletal class, and anthropometric parameters. Materials and Methods . Lateral cephalograms were obtained from 117 healthy young adult Lebanese subjects. Nineteen cephalometric linear/angular measurements of the nasopharynx, oropharynx, and hypopharynx were recorded. Anthropometric parameters including body mass index and neck circumference were measured. Results . Significant differences were demonstrated for 12 out of the 19 parameters considered between genders. Uvula and tongue dimensions and the distances between epiglottis-posterior pharyngeal wall and epiglottis-posterior nasal spine were significantly larger in males. The anteroposterior inclination of the uvula and the distances between the uvula and posterior pharyngeal wall were significantly greater in females. No significant differences were found between skeletal classes relative to most of the variables. Body mass index and neck circumference were positively correlated with the dimensions of tongue and uvula. Conclusions . Sexual dimorphism relative to some cephalometric variables and anthropometric parameters may account partly for larger oronasopharyngeal spaces in females. Anthropometric data need to be accounted for in population-related comparisons.